MEDIA PEMBELAJARAN KERANGKA TUBUH MANUSIA DENGAN METODE SELF DIRECT LEARNING UNTUK SISWA KELAS 4 SD SEMESTER 1 - Hajar Nuris Sofa (Pixel :Jurnal Ilmiah Komputer Grafis, 2018)
Rapid technological advances have a strong influence on various fields of life, one of which is the field of education. In the field of computer education is a familiar tool for use in the learning process. An educational institution such as a school certainly needs a learning medium as one of the methods in the teaching and learning process. SDN 4 Krajan Kulon is one of the educational institutions that always strives to improve quality both in terms of achievement and service. SDN 4 Krajan Kulon needs a learning media that can support the learning process to improve student performance that is still lacking, especially in science subjects. The solution offered in this study is a learning media with self direct learning method that makes it easy for users to understand the material being studied. This research uses the Research and Development (RnD) product development method, using 6 out of 10 research stages, namely potential and problems, data collection, product design, design validation, design improvement and product trials. The results of this study are to produce learning media with the method of self-direct learning. As for the validity value of the media expert at 2.7 which is declared feasible, while the validity value of the material expert is 3.4 which is declared feasible, and increases the average grade of the class of students 4 SD is 12% from the initial average score of 71 to 83.56.